MAIN DIRECTIONS FOR INCREASING INVESTMENT ACTIVITY OF SMALL BUSINESS ENTITIES IN UZBEKISTAN - Maribjon Gopparov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides opinions on the main directions of supporting small businesses, creating a favorable investment environment and increasing the investment activity of business entities in Uzbekistan.